Listening to Mendelssohn: An Owner's Manual - Hurwitz, David (Amadeus Press, 2020)
The greatest musical prodigy since Mozart (some would say he was even greater), Felix Mendelssohn (1809–1847) excelled in everything he did, musical or otherwise, and during his brief life became Europe’s most respected and beloved composer. Yet no musician suffered more drastic swings in his posthumous reputation, and as a result Mendelssohn’s music was obscured by a host of extra-musical factors: changes in taste, the rise of nationalism, anti-Semitism, and contempt for Victorian culture. This “owner’s manual” offers a guide to Mendelssohn’s musical output, major and minor, providing points of entry into a large body of work, much of which remains far too little known. There’s much more to Mendelssohn than the “Italian” Symphony and the “Midsummer Night’s Dream” Overture, and a whole creative world of vivid, expressive, and fantastical music is ready for exploration.